Safety of workers carrying out construction works and the use of machinery - Petrović, Miloš Z.; Anđelić, Kristina R.; Živulović - Petrović, Marina G. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Protection when handling construction machinery and construction work is a significant and important factor in the whole complex process of construction. Careful handling to protect human lives and the environment as well as building materials themselves is necessary. Careful and good handling and performance can lead to financial savings and to avoiding additional costs. Protective measures to be taken are: protection from risk during construction and protection from exploitation of the danger of the object. This area is defined by strict legislation. The Law on safety and health at work prescribed measures whose implementation and enforcement ensure safety and health at work. In addition, the law governs the rights and obligations of employers and employees to allow for more complete implementation of safety measures at work. Analyses of legal provisions show that the responsibility for creating and maintaining safe work environment lies with both employers and employees, who, each in a manner appropriate to their role in the process of work, comply with the prescribed measures. In order to ensure that the provisions about health and safety at work are consistently implemented, there is the inspection of the implementation of the act, regulations made under the act, technical and other measures relating to safety and health at work, as well as the implementation of measures for safety and health at work prescribed by a general act of the employer, collective agreement or work contract. This inspection is performed by labor inspectors. In the process of inspection, the inspector should work to control safety and health at work in accordance with his jurisdiction and provisions prescribed by lawwhich also prescribes the obligations of the employer during inspection. If it is found out during the inspectionthat there are reasons that have caused an injury or led to the hazard to safety and health at work, the inspector shall order taking measures and actions to eliminate these causes, or take measures which may prevent the emergence of injuries and reduce or eliminate risks to safety and health at work. Under certain conditions, for the duration of the circumstances that led to the endangerment of the safety and health of employees, specifically prescribed by law, the inspector shall ban work at employer’s workplace . During the organization of a site it is necessary to take account of the place and manner of depositing building materials. The material resistant to external influences (timbering, formwork, reinforcement, concrete curbs, pipes, sand, etc.,. Is stored in the open space near the building or in the vicinity of work. In case of heavy rain, wind or frost, their protection must be provided by covering them with plastic sheets, paper or cloth. For the works performed in the open air under adverse climatic and atmospheric conditions, the employer provides the use of appropriate personal protective equipment, or equipment while performing work. A first-aid cabinetmust be set up at the construction site Before sent to the place of work, construction machines must be checked in terms of their proper functioning. Mechanization is placed along the road. Security of construction equipment shall be organized through the guardian office. The operator of construction machinery powered by an internal combustion engine must be protected from the harmful effects of exhaust gases. A location for operating self-propelled construction machines must be set up so that the machine operator has a clear overview of the field in which it moves. All self-propelled construction machinery must have devices for giving audible signals. Construction processes are complex and open systems, characterized by a number of different types of resources whose interactions as well as interactions with the environment generate frequent occurrence of health and safety risks with potentially severe consequences. Risks identified at one site may only partially appear at another site in the same form and other risks must be considered again. Unlike other industries, the product of the construction process is stationary and often unique. Construction is implemented in the open area where the process is exposed to weather conditions. Construction processes are characterized by complex influences of interested parties(investor, contractor and subcontractors, government, public, etc) with their goals being often mutually exclusive which is projected on the implementation process and the aspects of the operation. When a company that performs a process of construction is of high quality, the negative impact of interested parties is more mitigated and the process of managing the work is successful. A specificity of the construction process is reflected in the process of separation of the design and the construction phase thus generating safety risks that could be avoided in the design phase. This problem is partially solved by introducing a coordinator for security and safety in the design phase whose task is to avoid or minimize any risks arising from the adopted design solutions. Also, by a stricter control and by punishing non-compliance with laws and regulations, the protection of workers, the environment and materials can be brought to a higher level.